Investigation the Potential of Myopopone castanea Smith (Hymenoptera: Formicidae) as Bio-Agent of Oryctes rhinoceros (Coleoptera: Scarabaediae) in Oil Palm Plantations - Widihastuty, Widihastuty; Tobing, Maryani Cyccu; Utami, Sri; Munar, Asritanarni (PLANTA TROPIKA, 2024)
The Myopopone castanea Smith (Hymenoptera: Formicidae) is a predator of Oryctes rhinoceros Linn larvae, the main pest on oil palm plantations.  These predatory ants have potential as biological agents because they have similar niches to their prey. This research aimed to explore the presence and potential of M. castanea as bio-agents in oil palm plantations and obtain knowledge about the abiotic environment of Myopopone castanea ant nests. The research was conducted in oil palm plantations owned by PTPN 4 Adolina, PTPN 2 Pagar Merbau, and smallholder oil palm plantations in Binjai, North Sumatra Province.  Sampling was conducted using the purposive sampling method and as many as 10 sample points in each plantation. The results showed that the average temperature and humidity in the ant nests were 29.4 °C and 70.5%, respectively. The number of individual ants in a colony varied greatly in number and developmental stages. The predation potential of Myopopone castanea ants in the field reached 50.3% for five days of exposure in smallholder plantations and 46,9% in Adolina Plantation. This research could be the opportunity to use Myopopone castanea ants as a biological control for larvae Oryctes rhinoceros in oil palm plantations.